Conditional reprogramming of pediatric airway epithelial cells: A new human model to investigate early‐life respiratory disorders - Wolf, S.; Perez, G. F.; Mukharesh, L.; Isaza, N.; Preciado, D.; Freishtat, R. J.; Pillai, D.; Rose, M. C.; Nino, G. (Pediatric allergy and immunology, 2017)
Background Airway epithelial cells (AEC) are quite difficult to access in newborns and infants. It is critically important to develop robust life‐extended models to conduct translational studies in this age group. We propose the use of a recently described cell culture technology (conditionally reprogrammed cells—CRC) to generate continuous primary cell cultures from nasal and bronchial AEC of young children. Methods We collected nasal and/or bronchial AEC from a total of 23 subjects of different ages including newborns/infants/toddlers (0‐2 years; N = 9), school‐age children (4‐11 years; N = 6), and a group of adolescent/adult donors (N = 8). For CRC generation, we used conditioned medium from mitotically inactivated 3T3 fibroblasts and Rho‐associated kinase (ROCK) inhibitor (Y‐27632). Antiviral immune responses were studied using 25 key antiviral genes and protein production of type III epithelial interferon (IFN λ1) after double‐stranded (ds) RNA exposure. Results CRC derived from primary AEC of neonates/infants and young children exhibited: (i) augmented proliferative capacity and life extension, (ii) preserved airway epithelial phenotype after multiple passages, (iii) robust immune responses characterized by the expression of innate antiviral genes and parallel nasal/bronchial production of IFN λ1 after exposure to dsRNA, and (iv) induction of airway epithelial inflammatory and remodeling responses to dsRNA (eg, CXCL8 and MMP9). Conclusion Conditional reprogramming of AEC from young children is a feasible and powerful translational approach to investigate early‐life airway epithelial immune responses in humans.